Negative life events and aggressive behavior of Efunsetan Aniwura (2012)
Proofs have emerged in Psychology that people with negative life events can be subjected to various anti-social behaviors, especially ones that are very aggressive and very inimical to the peace and order of the society. This paper examines the negative life events of Madam Efunsetan Aniwura and the consequential effects of such events on her behavior. It traces the history of the woman and examines the negative life events she experienced. The paper diagnoses the effects of her psychological problem on the society and the life end of this woman. Finally, it recommends the thorough examination of other pre-colonial personalities who shared similar life circumstances and using the findings to explain the current behaviours of the people undergoing the same or similar socio-psychological problems.